(untitled) (Physical Sciences and Technology, 2017)
Nuclear reactions in neutron star envelopes are considered in the frame of complex interactions stimulated by huge pressures in the overdense crystalline structures in the envelopes. It leads to the inclusion of forced reverse reactions that transform the nuclei to neutron-rich states and the appearance of free neutrons. The free neutrons in the structures cause resonance interactions with nuclei that fixed in nodes of crystal. The neutron re-scattering on subsystem of few nucleus at the energy near the energy of resonance level of the nucleus creates the few-body resonances, which depend on the distances between the nuclei.